Preparation method and use method of bleeding inhibition microspheres for concrete
By preparing water-exposed inhibitory microspheres with capillary pore structure, the problems of strength reduction and volume instability caused by concrete water-exposed are solved, and the mechanical properties and volume stability of concrete are improved, while improving the mixing and ease of mixing and Steel slag resources were utilized.
Patent Information
- Application Number
- CN202411623067.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
Concrete is prone to water discharge after pouring, resulting in a decrease in strength and unstable volume. The existing water-retaining agents have problems such as reduced slump and poor mixing and ease in improving water discharge.
A method of preparing a concrete water-inhibiting microspheres is adopted, and the preparation of alkali-soluble polyester fiber, sodium alginate, sodium silicate and steel slag micro powder is made through ultrasonic dispersion, peristaltic pump dropwise addition, reaction and filtration. Hydrotriosis inhibitory microspheres with capillary pore structures are produced.
This method not only effectively reduces the water leakage of concrete, improves the mechanical properties and volume stability of concrete, but also improves the fluidity and cohesiveness of concrete mixing materials, and realizes the resource utilization of steel slag.
Smart Images

Figure BDA0005133959690000021 
Figure BDA0005133959690000101 
Figure BDA0005133959690000111
Abstract
Description
Technical Field
[0001] The invention relates to the field of building construction, and in particular to a preparation method and a use method of water seepage inhibition microspheres for concrete. Background Art
[0002] Bleeding of concrete refers to the phenomenon that water appears on the surface of concrete after pouring and vibrating to make it dense. Bleeding occurs because the water retention capacity of the constituent materials is poor when the heavier solid components settle, so that part of the mixing water is in a dispersed state. Some of the rising water accumulates under the aggregate to form water pockets, further weakening the transition zone between cement paste and aggregate, and significantly affecting the strength of hardened concrete. After concrete is poured in a dry environment, the exuded water that moves upward to the top will gradually evaporate. If the surface of the concrete is exposed to wind, the evaporation rate of the exuded water will be greatly accelerated. If the evaporation rate is greater than the exudation rate, the surface concrete water content will decrease, and the concrete will shrink. At this time, the surface area of the concrete is constrained to produce tensile strain, and its tensile strength is almost zero, so plastic cracking will occur. Therefore, the bleeding of concrete has an extremely adverse effect on the strength and volume stability of concrete. Therefore, it is very important to control the bleeding of concrete.
[0003] There are many reasons for the bleeding of concrete, including poor compatibility between admixtures and cement, poor quality of raw materials, poor grading of aggregates, unreasonable sand ratio, etc. When the raw materials are fixed, adding water retaining agent to improve the segregation of concrete bleeding is a good way. However, water retaining agent mainly absorbs free water to alleviate the segregation of concrete bleeding. It mainly controls the migration of free water through adsorption and bridging, and has limited improvement on the workability of the mixture. In most cases, excessive adsorption of free water even reduces the slump of concrete, which is not conducive to its workability, and has no obvious improvement effect on the "bottom grabbing" and "sticky shovel" phenomena of concrete mixtures. Therefore, it is necessary to optimize the method of effectively controlling the bleeding of concrete mixtures. Summary of the invention
[0004] In view of the adverse effects existing in the current methods for improving the bleeding problem of concrete, the present invention prepares a bleeding inhibition microsphere for concrete. The use of the bleeding inhibition microsphere can not only significantly reduce the bleeding of concrete, but also is beneficial to improve the fluidity and cohesion of the concrete mixture, and improve the mechanical properties and volume stability of the concrete.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] A method for preparing microspheres for inhibiting bleeding of concrete comprises the following steps:
[0007] (1) weighing alkali-soluble polyester fiber and sodium dodecyl sulfate, adding them into water, and ultrasonically dispersing and stirring them continuously to make them dispersed evenly to form an alkali-soluble polyester fiber mixed solution A;
[0008] (2) Weigh high modulus sodium silicate and completely dissolve it in water, then add steel slag powder and stir evenly to form a uniform calcium silicate-steel slag powder suspension B;
[0009] (3) adding the mixed solution A in step (1) and the suspension B in step (2) into the container at equal speeds by a peristaltic pump to form a mixed solution C, stirring while adding until the mixture is uniform; then adding sodium alginate into the mixed solution C, stirring until it is completely dissolved, and continuing to stir for 5 to 10 minutes to make it evenly dissolved in the solution to form a mixed solution D;
[0010] (4) blowing the mixed solution D obtained in step (3) into an excess calcium nitrate solution through a peristaltic pump, then slowly stirring the solution to prevent it from settling to the bottom, reacting for 6 to 8 hours, controlling the reaction temperature at 60 to 80° C., and filtering to obtain gel microspheres;
[0011] (5) pouring the gel microspheres obtained in step (4) into an excess sodium citrate solution, stirring and dissolving for more than 30 minutes, and filtering out the particles; adding excess sodium citrate to allow the calcium alginate to be completely dissolved;
[0012] (6) Pour the particles obtained in step (5) into a sodium hydroxide solution, raise the temperature to 120-140° C., react for 4-6 hours, obtain the filtrate, wash and dry, and obtain the water exudation inhibiting microspheres.
[0013] Furthermore, the mass fractions of the above-mentioned raw material components of the present invention are as follows:
[0014]
[0015] The amount of water used in step (1) and step (2) is 100 parts by weight;
[0016] The effective content of calcium nitrate in the excess calcium nitrate solution in step (4) is not less than 1.5 times the total mass of sodium silicate and sodium alginate, and the mass concentration of the calcium nitrate solution is 1% to 2%.
[0017] Furthermore, the alkali-soluble polyester fiber in step (1) of the present invention has a length of 3 to 5 mm and a diameter of 5 to 40 nm.
[0018] Furthermore, the ultrasonic conditions in step (1) of the present invention are: power of 30 to 80 W, time of not less than 5 min;
[0019] Furthermore, the modulus of the sodium silicate in step (2) of the present invention is 2.5 to 3.7; the present invention adopts high modulus sodium silicate in order to increase the viscosity of the solution and the density of silicate in the solution, promote the formation of calcium silicate, and improve the strength of the microsphere structure; and when the sodium silicate dosage is too high, it is difficult to dissolve, the solution viscosity is too high, which is not conducive to uniform dispersion, and the mixing with the fiber is not uniform enough to form regular microspheres, so the dosage is controlled not to exceed 30 parts.
[0020] Furthermore, the specific surface area of the steel slag powder in step (2) of the present invention is not less than 600m 2 / kg, if the specific surface area is too small, its activity will not be sufficiently stimulated.
[0021] Furthermore, the droplet size of the mixed liquid D blown out from the pump port of the peristaltic pump in step (4) of the present invention is 1 to 2 mm. The purpose of using the peristaltic pump is to form the mixed liquid D into droplets of a certain size, and then pass it into the calcium salt solution, and then the sodium alginate is quickly converted into calcium alginate to form gel-state microspheres.
[0022] The reaction time in step (4) of the present invention is 6 to 8 hours. The purpose is to require a longer reaction time to ensure that the calcium ions in the solution have sufficient time to slowly penetrate into the solution microspheres wrapped by calcium alginate, so as to promote the calcium silicate to form a network cross-linked structure to constitute the main structure of the microspheres. The microspheres formed in a shorter time are smaller and the framework structure is weak. A longer time is unnecessary and may cause damage to the calcium alginate wrapping structure layer.
[0023] Furthermore, the mass concentration of the sodium citrate solution in step (5) of the present invention is 5%, and the purpose of adding sodium citrate is to dissolve calcium alginate.
[0024] The purpose of step (6) of the present invention is to dissolve the alkali-soluble polyester fiber. After the above steps (3) and (4) are mixed, the calcium ions in the formed calcium alginate microspheres react with sodium silicate to generate calcium silicate and sodium hydroxide. Because they are wrapped by calcium alginate, they penetrate into the microspheres, so that the microspheres contain a large amount of sodium hydroxide. When the temperature is raised to 120-140°C, the fibers can begin to dissolve rapidly in the alkaline solution of sodium hydroxide, releasing a large number of interconnected capillaries; if the temperature is not raised to this level, the alkali-soluble polyester fiber cannot be completely dissolved, the capillaries are blocked by the fibers, and the water absorption and storage function cannot be achieved; and under this condition and the high alkali solution condition, the active substances in the steel slag can be quickly dissolved, and the purpose of limiting the temperature reaction time is to allow the fibers to be completely dissolved and dissolved, and the active substances are gradually stimulated.
[0025] Furthermore, the water bleeding inhibition microsphere structure obtained in step (6) of the present invention is a spherical structure, and its size is between 0.075 mm and 2 mm.
[0026] The water-inhibiting microspheres obtained by the present invention have a capillary structure formed by calcium silicate / sodium silicate / active steel slag powder as the main structure, and have a strong ability to absorb water. The water-inhibiting microspheres of the present invention are soaked in a low concentration (mass concentration of 0.1-0.3%) sodium alginate solution in advance to fully absorb water before use. The diameter of the water-inhibiting microspheres in a saturated water state after absorbing water is 0.5-2 mm. When used, the water-inhibiting microspheres in a saturated water state are first mixed evenly with the cementitious material, and then the aggregate, water and admixture are added successively for stirring; the dosage of the water-inhibiting microspheres in a saturated water state is controlled at 10-20% of the mass of the cementitious material, and the workability of the concrete is greatly improved through the ball effect and lubrication effect, and a large amount of water is absorbed in advance through its own water absorption to avoid water segregation; wherein 40%-50% by mass of the water-inhibiting microspheres in a saturated water state replace fine aggregates, and 50%-60% by mass of the water-inhibiting microspheres in a saturated water state replace cementitious materials. This can better ensure that under the condition that the microspheres absorb a large amount of water, the slump of the concrete mixture is improved through the morphological effect and micro-aggregate effect, so that the state of the mixture will not deteriorate due to the decrease of free water.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The present invention realizes the resource utilization of steel slag. Steel slag has low activity. Under the combined action of alkaline solution and high temperature, it undergoes crystal transformation into active substances, which can promote the reaction and the structural filling of calcium silicate. In particular, the free calcium oxide and free magnesium oxide in the steel slag can also be filled in the pores through expansion, eliminating the adverse effects of the free calcium oxide and free magnesium oxide in the steel slag on concrete. At the same time, the filling effect transforms the pores inside the microspheres into ultra-micropores and dense structures, reducing the water absorption of the microspheres, which is beneficial to the improvement of the mechanical properties and volume stability of the concrete.
[0029] (2) The present invention generates calcium silicate by reacting sodium silicate with calcium nitrate / calcium salt. However, since sodium alginate and calcium ions form calcium alginate microspheres wrapped on the outside, the thickness of the generated calcium alginate film is effectively controlled by controlling the concentration of the sodium alginate solution, and the rate at which calcium ions in the solution penetrate into the interior can be cleverly controlled, so that calcium silicate is slowly generated on the surface of the alkali-soluble polyester fiber and gradually forms a microsphere structure. In addition, due to the presence of the alkali-soluble polyester fiber, the formed microsphere contains a large amount of alkali-soluble polyester fiber. At the same time, because sodium silicate reacts with calcium ions, the concentration of sodium hydroxide in the solution increases and is wrapped inside the microsphere. The microsphere is further placed in a sodium hydroxide solution and heated to 120-140° C., so that the alkali-soluble polyester fiber inside the generated microsphere is dissolved. At the same time, the activity of the steel slag is stimulated under high alkalinity and high temperature conditions, generating volcanic ash activity, thereby forming microsphere structure particles with a certain activity containing a large number of interconnected capillary structures.
[0030] (3) The water-inhibiting microspheres are passed through a low-concentration sodium alginate solution, and rely on their own capillary pore structure to quickly absorb water and low-concentration sodium alginate. When applied to concrete, a large amount of calcium ions are generated during the hydration reaction of cement in the concrete, so that a layer of calcium alginate (obtained by replacing calcium ions with sodium alginate) is wrapped on the outer surface of the microspheres. The calcium ions can only gradually and slowly penetrate into the interior, and the interior contains a large amount of sodium hydroxide, calcium silicate, and silicon-aluminum active substances dissolved from steel slag, which react to generate hydrated calcium silicate, hydrated calcium aluminosilicate, and other substances, which fill and block the capillaries while forcing the internal water to gradually overflow and further participate in the hydration reaction of cement. After the capillaries are blocked, ultra-micropores are formed or blocked densely, thereby improving the structural strength and volume stability of the microspheres.
[0031] (4) Capillaries will increase the shrinkage of concrete and reduce its volume stability. Therefore, sodium silicate and silicon-aluminum active substances in steel slag are used to induce the formation of hydration products in the microsphere capillaries. The calcium ions in calcium alginate gradually penetrate into the interior to reduce its water retention. At the same time, the calcium ions gradually react with the active substances and sodium silicate inside to generate hydration products that fill the structure, so that its capillaries are transformed into ultra-micropores and dense structures, which is conducive to the improvement of strength, durability and volume stability. At the same time, during the reaction process, due to the reduction of internal pores, water gradually and slowly seeps out through the calcium alginate gel to ensure the continuous hydration of cement.
[0032] (5) The water seepage inhibiting microspheres prepared by the present invention, when used in concrete, can store water in the concrete mixture inside the concrete structure to avoid the occurrence of segregated water seepage, while ensuring the workability of the mixture by utilizing the microsphere structure morphology effect and micro-aggregate filling effect. In the later stage, the water is released to ensure the normal hydration of cement, thereby improving the strength of the concrete structure. At the same time, the steel slag slowly releases active substances to induce the formation of hydration products in the pores, thereby filling and compacting the pores, avoiding the adverse effects of the pores on the volume stability, strength and durability of the concrete, and finally realizing the resource utilization of the steel slag. DETAILED DESCRIPTION
[0033] Hereinafter, embodiments of the present invention will be described in detail. However, the present invention may be implemented in many different forms, and the present invention should not be construed as being limited to the specific embodiments set forth herein. On the contrary, these embodiments are provided to explain the principles of the present invention and their practical applications, so that other persons skilled in the art can understand the various embodiments of the present invention and the various modifications suitable for specific intended applications.
[0034] The parts of each component in each example are in parts by mass.
[0035] The reference concrete used in the following embodiments and comparative examples is the concrete mix described in the blank example.
[0036] Blank example
[0037] The blank concrete mix ratio is shown in Table 1.
[0038] Table 1 Concrete mix ratio (kg / m 3 )
[0039] cement Fly ash Mineral powder sand gravel water Admixtures 352 44 44 739 1063 158 8.8
[0040] Example 1
[0041] A method for preparing microspheres for inhibiting bleeding of concrete comprises the following steps:
[0042] (1) Weigh 20 parts of alkali-soluble polyester fibers with a length of 5 mm and a diameter of 40 nm and 0.02 parts of sodium dodecyl sulfate, add them to 100 parts of water, and disperse them by ultrasonication while stirring continuously to form a mixed solution A;
[0043] (2) Weigh 30 parts of sodium silicate with a modulus of 3.7 and completely dissolve it in 100 parts of water. Then add 20 parts of steel slag powder (specific surface area 635 m 2 / kg) and stirred evenly to form suspension B.
[0044] (3) The mixed solution in step (1) and the suspension in step (2) are added dropwise to a container at equal speeds by a peristaltic pump to form a mixed solution C, and the mixture is stirred while being added until it is uniformly stirred (this method can ensure that A and B are uniformly mixed); then, 0.8 parts of sodium alginate is added to the mixture, and the mixture is stirred until it is completely dissolved, and the stirring is continued for 5 minutes to make it uniformly dissolved in the solution to form a mixed solution D;
[0045] (4) The mixed solution D is blown into a calcium nitrate solution with an excess concentration of 2% (the effective content of calcium nitrate is 50 parts) through a peristaltic pump, and the liquid droplet size of the mixed solution D blown out from the pump port is required to be 2 mm; then, the solution is slowly stirred to avoid sedimentation, and the reaction is carried out for 8 hours. The reaction temperature is controlled at 80° C. and the microspheres are obtained after filtration;
[0046] (5) pouring the microspheres obtained in step (4) into 100 parts of 5% sodium citrate solution, stirring and dissolving for 30 minutes, and filtering to obtain particles;
[0047] (6) Pour the particles in step (5) into a sodium hydroxide solution, heat to 120° C., react for 4 hours, obtain the filtrate, wash and dry, and obtain water-inhibiting microspheres.
[0048] The method of using the above-mentioned water-inhibiting microspheres is as follows:
[0049] (1) Soak the product in 0.3% sodium alginate solution before use to fully absorb water;
[0050] (2) Weigh the microspheres to make 20% of the total amount of cementitious materials. When using, mix the microspheres and cementitious materials evenly, then add aggregate, water and admixtures in sequence and stir; 40% of the microspheres replace fine aggregates, and 60% of the microspheres replace cementitious materials.
[0051] Example 2
[0052] A method for preparing microspheres for inhibiting bleeding of concrete comprises the following steps:
[0053] (1) Weigh 25 parts of alkali-soluble polyester fibers with a length of 3 mm and a diameter of 5 nm and 0.1 parts of sodium dodecyl sulfate, add them to 100 parts of water, and disperse them by ultrasonication while stirring continuously to form a mixed solution A;
[0054] (2) Weigh 25 parts of sodium silicate with a modulus of 2.5 and completely dissolve it in 100 parts of water. Then add 15 parts of steel slag powder (specific surface area 750 m 2 / kg) and stirred evenly to form suspension B.
[0055] (3) The mixed solution in step (1) and the suspension in step (2) are added dropwise to a container at equal speeds by a peristaltic pump to form a mixed solution C, and stirred while adding until the mixture is uniformly stirred; then, 1.2 parts of sodium alginate is added to the mixture, stirred until it is completely dissolved, and stirred for 10 minutes to make it evenly dissolved in the solution to form a mixed solution D;
[0056] (4) The mixed solution D is blown into a 1% excess concentration calcium nitrate solution (effective content of calcium nitrate is 40 parts) through a peristaltic pump, and the liquid droplet size of the mixed solution D blown out from the pump port is required to be 1 mm; then, the solution is slowly stirred to avoid sedimentation, reacted for 6 hours, the reaction temperature is controlled at 60°C, and the microspheres are obtained after filtration;
[0057] (5) pouring the microspheres obtained in step (4) into 80 parts of 5% sodium citrate solution, stirring and dissolving for 30 minutes, and filtering to obtain particles;
[0058] (6) Pour the particles in step (5) into a sodium hydroxide solution, heat to 140° C., react for 6 hours, obtain the filtrate, wash and dry, and obtain water-inhibiting microspheres.
[0059] The method of using the above-mentioned water-inhibiting microspheres is as follows:
[0060] (1) Soak the product in 0.1% sodium alginate solution before use to fully absorb water;
[0061] (2) Weigh the amount of microspheres to be 10% of the total amount of cementitious materials. When using, mix the microspheres and cementitious materials evenly, then add aggregate, water and admixtures in sequence and stir. 50% of the microspheres replace fine aggregates and 50% of the microspheres replace cementitious materials.
[0062] Example 3
[0063] A method for preparing microspheres for inhibiting bleeding of concrete comprises the following steps:
[0064] (1) Weigh 23 parts of alkali-soluble polyester fibers with a length of 4 mm and a diameter of 20 nm and 0.08 parts of sodium dodecyl sulfate, add them to 100 parts of water, and disperse them by ultrasonication while stirring continuously to form a mixed solution A;
[0065] (2) Weigh 28 parts of sodium silicate with a modulus of 3.0 and completely dissolve it in 100 parts of water. Then add 18 parts of steel slag powder (specific surface area of 680 m 2 / kg) and stirred evenly to form suspension B;
[0066] (3) The mixed solution in step (1) and the suspension in step (2) are added dropwise to a container at equal speeds by a peristaltic pump to form a mixed solution C, and stirred while adding until the mixture is uniformly stirred; then, 1.0 part of sodium alginate is added to the mixture, stirred until it is completely dissolved, and stirred for 8 minutes to make it evenly dissolved in the solution to form a mixed solution D;
[0067] (4) The mixed solution D is blown into a calcium nitrate solution with an excess concentration of 1.5% (the effective content of calcium nitrate is 60 parts) through a peristaltic pump, and the liquid droplet size of the mixed solution D blown out from the pump port is required to be 1.5 mm; then the solution is slowly stirred to avoid sedimentation, and the reaction is carried out for 7 hours. The reaction temperature is controlled at 70°C, and the microspheres are obtained after filtration;
[0068] (5) pouring the microspheres obtained in step (4) into 100 parts of 5% sodium citrate solution, stirring and dissolving for 30 minutes, and filtering to obtain particles;
[0069] (6) Pour the particles in step (5) into a sodium hydroxide solution, heat to 130° C., react for 5 hours, obtain the filtrate, wash and dry, and obtain water-inhibiting microspheres.
[0070] The method of using the above-mentioned water-inhibiting microspheres is as follows:
[0071] (1) When using, soak the microspheres in a 0.2% sodium alginate solution to fully absorb water (the water absorbed by the microspheres should be deducted when used in concrete);
[0072] (2) Weigh the amount of microspheres to be 15% of the total amount of cementitious materials. When using, mix the microspheres and cementitious materials evenly, then add aggregate, water and admixtures in sequence and stir. 45% of the microspheres replace fine aggregates, and 55% of the microspheres replace cementitious materials.
[0073] Comparative Example 1
[0074] The difference from Example 3 is that the length of the alkali-soluble polyester fiber is 8 mm.
[0075] Comparative Example 2
[0076] The difference from Example 3 is that the length of the alkali-soluble polyester fiber is 1 mm.
[0077] Comparative Example 3
[0078] The difference from Example 3 is that the diameter of the alkali-soluble polyester fiber is 1 nm.
[0079] Comparative Example 4
[0080] The difference from Example 3 is that the diameter of the alkali-soluble polyester fiber is 60 nm.
[0081] Comparative Example 5
[0082] The difference from Example 3 is that the diameter of the alkali-soluble polyester fiber is 200 nm.
[0083] Comparative Example 6
[0084] The difference from Example 3 is that the amount of alkali-soluble polyester fiber added in step (1) is 10 parts.
[0085] Comparative Example 7
[0086] The difference from Example 3 is that the amount of alkali-soluble polyester fiber added in step (1) is 30 parts.
[0087] Comparative Example 8
[0088] The difference from Example 3 is that the amount of sodium silicate added is 20 parts.
[0089] Comparative Example 9
[0090] The difference from Example 3 is that the amount of steel slag added is 30 parts.
[0091] Comparative Example 10
[0092] The difference from Example 3 is that the amount of steel slag added is 5 parts.
[0093] Comparative Example 11
[0094] The difference from Example 3 is that the specific surface area of the steel slag is 328m 2 / kg.
[0095] Comparative Example 12
[0096] The difference from Example 3 is that 0.5 parts of sodium alginate is added in step (3).
[0097] Comparative Example 13
[0098] The difference from Example 3 is that 2 parts of sodium alginate are added in step (3).
[0099] Comparative Example 14
[0100] The difference from Example 3 is that 0.5% calcium nitrate solution is added in step (4).
[0101] Comparative Example 15
[0102] The difference from Example 3 is that 2% calcium nitrate solution is added in step (4).
[0103] Comparative Example 16
[0104] The difference from Example 3 is that the reaction temperature in step (4) is room temperature 20°C.
[0105] Comparative Example 17
[0106] The difference from Example 3 is that the reaction temperature in step (4) is room temperature 100°C.
[0107] Comparative Example 18
[0108] The difference from Example 3 is that the reaction temperature in step (4) is room temperature 100°C.
[0109] Comparative Example 19
[0110] The difference from Example 3 is that in step (7), clean water is used for soaking instead of a low concentration sodium alginate solution.
[0111] Comparative Example 20
[0112] The difference from Example 3 is that 0.5% sodium alginate solution is added in step (4).
[0113] Comparative Example 21
[0114] The difference from Example 3 is that in step (8), microspheres are used to completely replace sand.
[0115] Comparative Example 22
[0116] The difference from Example 3 is that in step (8), microspheres are used to completely replace the gelling material.
[0117] The concrete properties obtained in the above embodiments and comparative examples are shown in Table 2.
[0118] Table 2 Concrete properties of various embodiments and comparative examples
[0119]
[0120]
[0121] From the data in Table 2, we can find that:
[0122] In Comparative Example 1, when the length of the alkali-soluble polyester fiber increases, the water bleeding rate increases, the pressure water bleeding rate increases, the strength decreases compared with the benchmark, and decreases significantly compared with Example 3. At the same time, the shrinkage rate increases significantly compared with Example 3. This is mainly because the fiber length is too long, resulting in poor dispersibility in the solution, and curling and entanglement are prone to occur, resulting in a large number of connected capillaries with excessively large pore sizes in the generated microspheres. Although the water bleeding rate and pressure water bleeding rate of the concrete are significantly improved, these connected capillaries are not densely filled in the later stage of concrete hardening, which is not conducive to the improvement of the compressive strength of the concrete and the improvement of the shrinkage rate.
[0123] In Comparative Example 2, compared with Example 3, the water bleeding rate and pressure water bleeding rate increased, the compressive strength decreased, and the shrinkage rate increased; compared with the benchmark concrete, the water bleeding rate, pressure water bleeding rate, compressive strength and shrinkage rate (volume stability) were all improved; this shows that the use of alkali-soluble polyester fiber can improve the water bleeding rate, strength and volume stability of concrete, but the fiber is too short, which makes it easy for the microspheres to be completely embedded in the fibers when they grow, blocking the connected capillaries, thereby reducing the water absorption of the microspheres, affecting the water bleeding rate and pressure water bleeding rate, and also resulting in no obvious improvement in strength and no obvious improvement in shrinkage.
[0124] In Comparative Example 3, compared with Example 3, the water bleeding rate and pressure water bleeding rate increased significantly, the compressive strength decreased significantly, and the shrinkage rate increased significantly; compared with the benchmark concrete, the water bleeding rate, pressure water bleeding rate, and shrinkage rate (volume stability) were improved, but the improvement effect was not obvious, and the compressive strength decreased. This shows that the use of alkali-soluble polyester fibers with too fine diameters is not conducive to improving the performance of concrete. This is mainly because the fiber diameter is too fine, mainly generating ultra-micropores, and the water absorption is reduced, so it cannot play a good role in absorbing and storing water in the early stage, and after replacing the cementitious material, the cementitious material is reduced, resulting in a decrease in strength.
[0125] In Comparative Example 4, compared with Example 3, the difference in water bleeding rate and pressure water bleeding rate is not large, but the compressive strength is significantly reduced and the shrinkage rate is significantly increased; this is mainly because when the fiber diameter is 60nm, it is still a capillary pore with extremely strong water absorption, so it will reduce the water bleeding rate and pressure water bleeding rate of concrete, but because the fiber diameter is relatively large, the pore diameter is large, even if hydration products are produced under the induction of active substances in the microspheres in the later stage, the pore diameter cannot be completely filled, and there are still a large number of micro capillaries, which causes the concrete shrinkage to increase and the volume stability to decrease; and because the filled micro capillaries still have strong water absorption, the release of free water is reduced, and the cement hydration is insufficient. The above combined reasons cause the strength to decrease.
[0126] In Comparative Example 5, compared with Example 3, the water bleeding rate and pressure water bleeding rate increased, the compressive strength decreased, and the shrinkage rate increased significantly. However, compared with the benchmark concrete, the shrinkage rate did not change much, the strength did not decrease significantly, and the water bleeding rate and pressure water bleeding rate improved. This is mainly because when the fiber diameter is 200nm, the capillary osmotic pressure becomes smaller and the water absorption becomes weaker, so the microspheres will release more free water than in Example 3, resulting in an increase in the water bleeding rate and pressure water bleeding rate. However, this type of pore size has a relatively small effect on the shrinkage and strength of concrete, so the shrinkage rate does not change much, but due to the replacement of part of the cementitious material, the strength is reduced.
[0127] In Comparative Example 6, compared with Example 3, the bleeding rate and pressure bleeding rate increased, the compressive strength decreased, and the shrinkage rate increased; compared with the benchmark concrete, the bleeding rate, pressure bleeding rate, compressive strength and shrinkage rate (volume stability) were all improved. This shows that the use of alkali-soluble polyester fiber can improve the bleeding rate, strength and volume stability of concrete, but the amount is too small, resulting in fewer capillaries in the microspheres, which reduces the water absorption of the microspheres, affects the bleeding rate and pressure bleeding rate, and then has an adverse effect on the strength and volume stability of the concrete.
[0128] In Comparative Example 7, compared with Example 3, when the amount of alkali-soluble polyester fiber increased, the water bleeding rate increased slightly, the pressure water bleeding rate increased slightly, and the strength decreased significantly. This is mainly because excessive fiber content leads to poor dispersibility in the solution and agglomeration, resulting in a large number of connected capillaries with excessively large pores in the generated microspheres. Although there is a significant improvement effect on the water bleeding rate and pressure water bleeding rate of concrete, these connected capillaries are not densely filled in the later stage of concrete hardening, which is not conducive to the improvement of concrete compressive strength and shrinkage rate. At the same time, excessive fiber content is likely to have an adverse effect on the structural strength of the microspheres and will also have an adverse effect on the mechanical properties of concrete.
[0129] In Comparative Example 8, compared with Example 3, when the sodium silicate dosage is low, the water bleeding rate remains unchanged, the pressure water bleeding rate increases slightly, and the strength decreases significantly. This is mainly because the low sodium silicate dosage leads to a decrease in the silicate concentration, a smaller size of the generated microspheres, and a decrease in the strength of the microsphere structure. Therefore, although the water bleeding rate remains unchanged, the pressure water bleeding rate increases, which also causes a decrease in strength.
[0130] In Comparative Example 9, compared with Example 3, when the steel slag content is high, the water bleeding rate remains unchanged, the pressure water bleeding rate increases slightly, and the strength decreases significantly. This is mainly because steel slag is an inert material, and excessively high content leads to a decrease in the strength of the microsphere structure, which also causes a decrease in strength.
[0131] In Comparative Example 10, compared with Example 3, when the steel slag content is low, the water bleeding rate remains unchanged, the pressure water bleeding rate is not much different, but the strength is significantly reduced and the shrinkage rate is significantly increased; this is because the steel slag content is too low, and less active substances can be stimulated in high temperature and sodium hydroxide solution in the later stage, and it cannot play a good induction role when used in concrete, and it is difficult to play a good capillary filling role in the pores, resulting in a large number of unfilled capillaries in the end, which is unfavorable to strength and volume stability.
[0132] In Comparative Example 11, compared with Example 3, when the specific surface area of the steel slag is too small and the particles are too large, the water bleeding rate remains unchanged, the difference in the pressure water bleeding rate is not large, but the strength is significantly reduced and the shrinkage rate is significantly increased; this is because the steel slag particles are too large, and less active substances can be stimulated in high temperature and sodium hydroxide solution in the later stage. When used in concrete, it cannot play a good inducing role, and it is difficult to play a good capillary filling role in the pores, resulting in a large number of unfilled capillaries in the end, which is unfavorable to the strength and volume stability.
[0133] It can be seen from the above Comparative Examples 9, 10 and 11 that the dosage and specific surface area of steel slag are crucial to its improvement, which is also an important prerequisite for realizing the utilization of steel slag.
[0134] In Comparative Example 12, compared with Example 3, the dosage of sodium alginate is too low, and the calcium ion penetration rate is too fast, which easily causes the reaction to intensify, and the microsphere particle structure and components formed are uneven, and the pore structure is uncontrollable, resulting in uncontrollable water absorption capacity and surface morphology, which in turn has an adverse effect on the performance of concrete.
[0135] In Comparative Example 13, compared with Example 3, when the sodium alginate dosage is too high, the water bleeding rate increases, the pressure water bleeding rate increases, the compressive strength decreases, and the shrinkage rate increases. This is mainly because the excessive sodium alginate leads to an increase in the thickness of the formed calcium alginate and the density of the cross-linked structure, resulting in a decrease in the speed and number of calcium ions penetrating into the calcium alginate microspheres, and a decrease in the support of the formed microsphere structure, which not only complicates the pore structure, reduces the water absorption, but also reduces the strength, ultimately leading to a decrease in the mechanical properties of the concrete and a decrease in volume stability.
[0136] In Comparative Example 14, compared with Example 3, the dosage of sodium alginate is too low, and the calcium ion penetration rate is too fast, which easily causes the reaction to intensify, and the microsphere particle structure and components formed are uneven, and the pore structure is uncontrollable, resulting in uncontrollable water absorption capacity and surface morphology, which in turn has an adverse effect on the performance of concrete.
[0137] In Comparative Example 15, compared with Example 3, when the calcium nitrate concentration is too high, the water bleeding rate increases, the pressure water bleeding rate increases, the compressive strength decreases, and the shrinkage rate increases. This is mainly because the high calcium nitrate concentration leads to an increase in the density of the cross-linked structure of calcium alginate formed, resulting in a decrease in the speed and number of calcium ions in the calcium nitrate solution penetrating into the calcium alginate microspheres, and a decrease in the support of the microsphere structure formed, which not only makes the pore structure complex, reduces the water absorption, but also reduces the strength, ultimately leading to a decrease in the mechanical properties of the concrete and a decrease in volume stability.
[0138] In Comparative Example 16, compared with Example 3, when the reaction temperature is room temperature, the water seepage rate of concrete increases, the pressure water seepage rate increases, the compressive strength decreases, and the shrinkage rate increases. This is mainly because the calcium alginate on the surface of the microspheres has a strong gelling property at room temperature, and as calcium ions gradually enter, the internal sodium alginate gradually transforms into calcium alginate, further enhancing the barrier effect of the calcium alginate gel. By controlling the temperature at 60-80°C, the viscosity of calcium alginate can be better controlled (high temperature can reduce the viscosity and gelling property of calcium alginate to a certain extent), ensuring the stable infiltration of calcium ions and participating in the reaction to form a microsphere structure.
[0139] In Comparative Example 17, compared with Example 3, the reaction temperature is too high, the calcium ion penetration rate is too fast, and the viscosity of calcium alginate is too low, which easily causes the reaction to intensify, the microsphere particle structure and components formed are uneven, the pore structure is uncontrollable, resulting in uncontrollable water absorption capacity and surface morphology, which in turn has an adverse effect on the performance of concrete.
[0140] In Comparative Example 18, compared with Example 3, the reaction temperature is too high, the calcium ion penetration rate is too fast, and the viscosity of calcium alginate is too low, which easily causes the reaction to intensify, the microsphere particle structure and components formed are uneven, the pore structure is uncontrollable, resulting in uncontrollable water absorption capacity and surface morphology, which in turn has an adverse effect on the performance of concrete.
[0141] In Comparative Example 19, compared with Example 3, the water immersion is improved, the compressive strength is reduced, and the shrinkage rate is increased. Because the purpose of sodium alginate immersion is to form a calcium alginate coating on the surface of the microspheres, it can retain water and prevent water from penetrating into the concrete slurry too quickly. Secondly, after the calcium ions penetrate deeply, the active substances of the slag can be relied on to react with water to fill the pores. When the calcium alginate microsphere structure is not formed on the surface, the calcium ions easily form hydration products on its surface to block the holes, hindering the slow overflow of the internal water in the later stage to participate in the cement hydration reaction, so that the cement hydration reaction is incomplete, the strength decreases, and the shrinkage increases. At the same time, the lack of the hindering effect of calcium alginate makes the water inside the microspheres easy to overflow, and quickly overflows under pressure conditions, resulting in an increase in the pressure water bleeding rate and the water bleeding rate.
[0142] In Comparative Example 20, compared with Example 3, the water bleeding rate and pressure water bleeding rate of concrete did not change much by using a sodium alginate solution with a higher concentration, but the strength decreased rapidly and the shrinkage rate also increased significantly. This is because the concentration of the sodium alginate solution is too high. As the cement hydration proceeds in the concrete mixture, the calcium ion concentration increases, resulting in the conversion of sodium alginate into a dense cross-linked structure of calcium alginate, which affects the infiltration of calcium ions and the seepage of water, which is not conducive to the filling of the microsphere pores and the continuous cement hydration. Therefore, the concentration of the sodium alginate solution should be controlled.
[0143] In Comparative Example 21, compared with Example 3, the slump is further increased, but the water bleeding rate and pressure water bleeding rate are also increased accordingly, and the strength and shrinkage rate are decreased. This is because the morphological effect and filling effect of the microsphere particles are conducive to the improvement of the state of the mixture, but excessive replacement of sand causes the adsorption rate of sand to free water to decrease, produces more free water, and causes unreasonable gradation of aggregates and cementitious materials, thereby affecting the compressive strength and shrinkage rate.
[0144] In Comparative Example 22, compared with Example 3, the slump is further increased, but the water seepage rate and pressure water seepage rate are also increased accordingly, and the strength is significantly reduced. This is because the amount of cement is reduced, and the morphological effect and filling effect of the microsphere particles are conducive to the improvement of the state of the mixture, but excessive replacement of cementitious materials leads to a decrease in strength. Therefore, when applied, its dosage and the proportion of raw materials replaced after addition should be reasonably controlled.
Claims
1. A method for preparing microspheres for inhibiting bleeding of concrete, characterized in that: The following steps are involved: (1) weighing alkali-soluble polyester fiber and sodium dodecyl sulfate, adding them into water, and ultrasonically dispersing and stirring them continuously to make them dispersed evenly to form an alkali-soluble polyester fiber mixed solution A; (2) Weigh high modulus sodium silicate and completely dissolve it in water, then add steel slag powder and stir evenly to form a uniform calcium silicate-steel slag powder suspension B; (3) adding the mixed solution A in step (1) and the suspension B in step (2) into the container at equal speeds by a peristaltic pump to form a mixed solution C, stirring while adding until the mixture is uniform; then adding sodium alginate into the mixed solution C, stirring until it is completely dissolved, and continuing to stir for 5 to 10 minutes to make it evenly dissolved in the solution to form a mixed solution D; (4) blowing the mixed solution D obtained in step (3) into an excess calcium nitrate solution through a peristaltic pump, then slowly stirring the solution to prevent it from settling to the bottom, reacting for 6 to 8 hours, controlling the reaction temperature at 60 to 80° C., and filtering to obtain gel microspheres; (5) pouring the gel microspheres obtained in step (4) into an excess sodium citrate solution, stirring and dissolving for more than 30 minutes to completely dissolve the calcium alginate, and filtering to obtain particles; (6) Pour the particles obtained in step (5) into a sodium hydroxide solution, raise the temperature to 120-140° C., react for 4-6 hours, obtain the filtrate, wash and dry, and obtain the water exudation inhibiting microspheres.
2. The method for preparing a water bleeding inhibition microsphere for concrete according to claim 1, characterized in that: The mass fractions of the above raw material components are as follows: 20-25 parts of alkali-soluble polyester fiber, 0.02-0.1 parts of sodium lauryl sulfate, 25-30 parts of sodium silicate, 15-20 parts of steel slag powder, 0.8-1.2 parts of sodium alginate, The amount of water used in step (1) and step (2) is 100 parts by weight; The effective content of calcium nitrate in the excess calcium nitrate solution in step (4) is not less than 1.5 times the total mass of sodium silicate and sodium alginate, and the mass concentration of the calcium nitrate solution is 1% to 2%.
3. The method for preparing the water bleeding inhibition microspheres for concrete according to claim 1, characterized in that: The alkali-soluble polyester fiber in step (1) has a length of 3 to 5 mm and a diameter of 5 to 40 nm; The ultrasonic conditions are: power of 30-80w, time not less than 5min.
4. The method for preparing the water bleeding inhibition microspheres for concrete according to claim 1, characterized in that: The modulus of the sodium silicate in step (2) is 2.5 to 3.7; The specific surface area of the steel slag powder is not less than 600m 2 / kg.
5. The method for preparing the water bleeding inhibition microspheres for concrete according to claim 1, characterized in that: The liquid droplet size of the mixed liquid D blown out from the pump port of the peristaltic pump in step (4) is 1 to 2 mm.
6. The method for preparing the water bleeding inhibition microspheres for concrete according to claim 1, characterized in that: The mass concentration of the sodium citrate solution in step (5) is 5%.
7. The method for preparing the water bleeding inhibition microspheres for concrete according to claim 1, characterized in that: The water-exudation-inhibiting microsphere structure obtained in step (6) is a spherical structure, and its size is between 0.075 mm and 2 mm.
8. A method for using the microspheres for inhibiting bleeding of concrete prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The water-inhibiting microspheres are soaked in a low-concentration sodium alginate solution in advance before being fully absorbed. The diameter of the water-inhibiting microspheres in a saturated water state after absorbing water is 0.5 to 2 mm. When used, the water-inhibiting microspheres in a saturated water state are first mixed evenly with the cementitious material, and then the aggregate, water and admixture are added in sequence for stirring.
9. The application method according to claim 8, characterized in that: The mass concentration of the low-concentration sodium alginate solution is 0.1-0.3%.
10. The application method according to claim 8, characterized in that: The content of the water-saturated water-inhibiting microspheres is controlled at 10-20% of the mass of the cementitious material, wherein 40-50% by mass of the water-saturated water-inhibiting microspheres replace fine aggregates, and 50-60% by mass of the water-saturated water-inhibiting microspheres replace cementitious materials.
Citation Information
Cited By
Green low-carbon cementing material for roadbed and preparation method of green low-carbon cementing material
CN120590136A